All Days 2000
DOI: 10.2118/65527-ms
|View full text |Cite
|
Sign up to set email alerts
|

Gel Water Shutoff in Fractured or Faulted Horizontal Wells

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractAdvancement in design and implementation of polymer gel water shutoff treatments in horizontal wells that penetrate fractures or faults have come from empirical improvements in the field and synergism between monitored field treatments and independent laboratory research. One case history will be detailed, followed by a summary of several other treatments.Simple calculations can give at least a rudimentary indication of the width of the fracture or fault that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Seright (2003) showed that once cured, CC/AP gel (a type of flowing gel) does not significantly leak off into porous rock with matrix permeability of 1.5 md in limestone core and 10,000 md in a polyethylene core during extrusion through a fracture of varying widths. High-molecular weight flowing gels have been shown to successfully reduce water production in producing wells (Borling, 1994;Demir et al, 2008;Lane and Seright, 2000;Moffitt, 1993;Wibowo et al, 1999). These gels are commonly placed by bullheading a certain volume into the reservoir, displacing them from the wellbore, and shutting in the well to allow curing (Lane, 1998;Southwell and Posey, 1994;Wibowo et al, 1999).…”
Section: Water Isolation Techniquementioning
confidence: 99%
“…Seright (2003) showed that once cured, CC/AP gel (a type of flowing gel) does not significantly leak off into porous rock with matrix permeability of 1.5 md in limestone core and 10,000 md in a polyethylene core during extrusion through a fracture of varying widths. High-molecular weight flowing gels have been shown to successfully reduce water production in producing wells (Borling, 1994;Demir et al, 2008;Lane and Seright, 2000;Moffitt, 1993;Wibowo et al, 1999). These gels are commonly placed by bullheading a certain volume into the reservoir, displacing them from the wellbore, and shutting in the well to allow curing (Lane, 1998;Southwell and Posey, 1994;Wibowo et al, 1999).…”
Section: Water Isolation Techniquementioning
confidence: 99%
“…This fact allows gel propagation along fractures to be predicted. 39,61 [See Figs. 2 and 3 for propagation of a Cr(III)-acetate-HPAM gel in a vertical fracture of fixed height.]…”
Section: Individual Fractures That Cause Channeling From Injectors Tomentioning
confidence: 99%
“…Injection of gels into formations containing fractures or channels (high permeability) has been studied extensively (Fielding et al 1994;Lane and Seright 2000;Sydansk and Southwell 2000;Wang et al 2001). Often, preformed gels (PGs) (instead of in-situ-formed gels) are preferred to avoid the difficulties associated with controlling gelation time and gel compositions during gel placement in porous media.…”
Section: Introductionmentioning
confidence: 99%